A review of bubble hair deformity. (29th April 2022) - Li, Yumeng M.; Diaz‐Perez, Julio A.; Obayomi, Aderonke; Galimberti, Fabrizio; Romanelli, Paolo; Tosti, Antonella
Abstract: Bubble hair deformity is an acquired abnormality characterized by air‐filled cavity formations within the hair shaft, usually because of heat damage. Traditionally, bubble hair is diagnosed by visualization of characteristic bubbles under light microscopy. The increased utilization of trichoscopy (scalp dermoscopy) has led to its adoption in the diagnosis of many hair and scalp conditions, including bubble hair deformity. We sought to review clinical reports evaluating the patient profile, use of diagnostic imaging, and treatment options for bubble hair deformity. A systematic search of PubMed was performed in February 2021 using various keywords. Titles and abstracts were screened, leading to the selection of 11 case reports or series. The majority of patients were middle‐aged Caucasian women who had used a heated tool to dry or style wet hair. Treatment consisted of cessation of heated tool usage. Light microscopy visualization of characteristic hair shaft cavities was used for diagnosis of bubble hair deformity in reports published prior to 2012. Diagnosis by trichoscopy was used in more recent reports. Our findings support the use of trichoscopy as a convenient and noninvasive method of diagnosing bubble hair deformity. More clinical studies are needed to evaluate the development of bubble hair deformity in ethnic hair.